Ler e falar a língua indígena Balatiponé dentro de seu contexto cultural - Quezo, Luciano Ariabo (Universidade Federal de São Carlos, 2022)
The core of this Master’s Thesis is to present a Didactic Sequence of reading and practice of the Balatiponé indigenous language for students from the 6th (sixth) year of Elementary School at the indigenous school of the Balatiponé territory to broaden the knowledge of this linguistic system. It aims to generate social repercussions with the indigenous community in which the research was conducted, thus taking advantage of the interest of young people and adults in expanding their knowledge regarding this language. Another position of considerable importance sought here is that this work can promote a profound meaning to the University from a political perspective, understanding that this scope has been demanded by research presented by indigenous people from their presence as students. Therefore, the production of this material reinforces this symbolic mark in contemporary Brazil, which is the advent of indigenous epistemology at the University presented by indigenous people more frequently in the last two decades. The first methodological steps of this research involved carrying out a bibliographical survey with indigenous teachers who have already released language materials, as well as linguistic records of non-indigenous researchers, in addition to making use of the author researcher's knowledge of their mother language. The second step was to dialogue with teachers who work in the languages area at the Julá Paré School in the Balatiponé territory to obtain better information about what is being built at the school in terms of Balatiponé language. The third step, based on the previous steps and with the exploration of the author’s models who carried out similar projects, builds a Didactic Sequence to read and speak the Balatiponé indigenous language. To contribute to strengthening the training of professionals in Indigenous Intercultural Basic Education, as well as for school education in the indigenous villages, encouraging the resumption of the Balatiponé indigenous culture and language.
Leer y hablar la lengua indígena Balatiponé dentro de su contexto cultural
Keywords: Balatiponé; Língua Indígena; Sequência Didática; Ensino de Língua; Indigenous language; Didactic Sequence; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA